Is 'first in family' a good indicator for widening university participation?. (October 2020) - Adamecz-Völgyi, Anna; Henderson, Morag; Shure, Nikki
Highlights: English universities use "first in family" as an indicator to increase the share of disadvantaged students. Being potential first in family is an important barrier to university participation and graduation and has strong predictive power compared to other sources of disadvantage. Conditional on prior attainment, the predictive power of potential first in family becomes relatively small. The disadvantage captured by first in family operates through early educational attainment which points to the need to use contextualised university entrance offers. Abstract: Universities use 'first in family' or 'first generation' as an indicator to increase the diversity of their student intake, but little is known about whether it is a good indicator of disadvantage. We use nationally representative, longitudinal survey data linked to administrative data from England to provide the first comprehensive analysis of this measure. We employ parametric probability (logit) and non-parametric classification (random forest) models to look at its relative predictive power of university participation and graduation. We find that being first in family is an important barrier to university participation and graduation, over and above other sources of disadvantage. This association seems to operate through the channel of early educational attainment. Our findings indicate that the first in family indicator could be key in efforts to widen participation at universities.